EFEKTIVITAS DAUN ZODIA (Evodia suaveolens) SEBAGAI REPELLENT NYAMUK AEDES AEGYPTI - Sudiarti, Made; Ahyanti, Mei; Yushananta, Prayudhy (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Dengue fever (DHF) is an infectious disease caused by the dengue virus through the Aedes aegypti mosquito vector. The use of repellents is an effort to prevent mosquito bites. One of the potential natural ingredients used as a repellent is zodia leaves (Evodia suaveolens) because they contain up to 46% linalool. This study aims to measure the effectiveness of the essential oil from zodia leaves as a repellent. The study was conducted on a laboratory scale following WHOPES recommendations. A total of 960 adult Ae.aegypti mosquitoes (aged 2-5 days) from the rearing process were used in this study. Five volunteers participated as probands. The essential oil is distilled from fresh azola leaves with 70% ethanol as solvent. The repellent lotion is made using an essential oil, lanolin, stearic acid, and other substance. The experiment used an arm-in-cage with two replication and 20 mosquitoes for each treatment. The concentrations tested were 1%, 2%, 3%, with 0% control. The number of mosquitoes that arrived was recorded after using the repellent for 15, 30, 60, 120, 240, and 360 minutes. The study found a significant effect of concentration (p-value <0.0001) and contact time (p-value <0.0001) on the number of mosquitoes that landed. Zodia leaf lotion (Evodia suaveolens) with a concentration of 3% can protect 50% up to 360 minutes after use. Further research is needed to get a concentration that can provide 95% protective power after 30 minutes of use and 90% after 360 minutes